Integrative genomic and functional characterization of halotolerant Bacillus paralicheniformis MHN12 for sustainable agriculture - Dahiya, Priyanka; Dhiman, Shruti; Kumar, Pradeep; Rani, Simran; Narayanan, A. Sankara; Arora, Kiran; Dang, Amita Suneja; Suneja, Pooja (Frontiers in Microbiology, 2026)
IntroductionThis study clarifies the taxonomic identity of Bacillus paralicheniformis MHN12 and maps the genetic foundations of its beneficial traits. It also provides functional insights into the salinity-stress response and paves the way for the development of MHN12 as a potential bioinoculant to enhance crop stress resilience and productivityMethodsThe endophytic strain MHN12, isolated from Vigna radiata, was initially identified as Bacillus licheniformis based on its 16S rRNA sequence. To ascertain its identity and ensure accurate taxonomic classification, a comparative genomic analysis based on genome relatedness indexes and secondary metabolite biosynthetic gene clusters was conducted, involving MHN12 and 22 other B. paralicheniformis strains.Results and discussionThere were high similarities among the strains and antiSMASH revealed the presence of biosynthetic gene clusters specifically fengycin and bacitracin in MHN12 encoded by the genomes of B. paralicheniformis but absent in B. licheniformis. The whole genome analysis of B. paralicheniformis MHN12, focusing on identifying genes contributing to its potential to promote plant growth and abiotic stress tolerance was also performed. Genes linked to chemotaxis, motility, polysaccharide synthesis, plant growth promoting traits, antimicrobial and stress mitigation compounds were annotated. This highlights MHN12's potential to efficiently colonize plants, stimulate their growth, and protect them from environmental stresses and pathogens. In vitro assays also supported the genomic data, demonstrating MHN12's ability to synthesize enzymatic antioxidants and exopolysaccharides (EPS) while retaining plant growth promoting traits under salinity stress. Gas chromatography (GC)-based analysis revealed modulation of plasma membrane lipids aiding MHN12 to combat salt stress.